Coagulation factor XIII: a multifunctional transglutaminase with clinical potential in a range of conditions - Dickneite, Gerhard; Herwald, Heiko; Korte, Wolfgang; Allanore, Yannick; Denton, Christopher P.; Cerinic, Marco Matucci (Thrombosis and Haemostasis, 2015)
Coagulation factor XIII (FXIII), a plasma transglutaminase, is best known as the final enzyme in the coagulation cascade, where it is responsible for cross-linking of fibrin. However, a growing body of evidence has demonstrated that FXIII targets a wide range of additional substrates that have important roles in health and disease. These include antifibrinolytic proteins, with cross-linking of α2-antiplasmin to fibrin, and potentially fibrinogen, being the principal mechanism(s) whereby plasmin-mediated clot degradation is minimised. FXIII also acts on endothelial cell VEGFR-2 and α2β3 integrin, which ultimately leads to downregulation of the antiangiogenic protein thrombospondin-1, promoting angiogenesis and neovascularisation. Under infectious disease conditions, FXIII cross-links bacterial surface proteins to fibrinogen, resulting in immobilisation and killing, while during wound healing, FXIII induces cross-linking of the provisional matrix. The latter process has been shown to influence the interaction of leukocytes with the provisional extracellular matrix and promote wound healing. Through these actions, there are good rationales for evaluating the therapeutic potential of FXIII in diseases in which tissue repair is dysregulated or perturbed, including systemic sclerosis (scleroderma), invasive bacterial infections, and tissue repair, for instance healing of venous leg ulcers or myocardial injuries. Adequate levels of FXIII are also required in patients undergoing surgery to prevent or treat perioperative bleeding, and its augmentation in patients with/at risk for perioperative bleeding may also have potential clinical benefit. While there are preclinical and/or clinical data to support the use of FXIII in a range of settings, further clinical evaluation in these underexplored applications is warranted.
Keywords: Coagulation; factor XIII; infection; scleroderma; wound healing